PERAN SOSIAL GURU PAI DALAM MASYARAKAT - HILAL, UMI ZAKIYATUL (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2019)
This research is motivated by the problem that PAI teachers pay less attention to their social competencies so that it impacts on the high / low role played in the environment of the communities around them. This research is a field research (qualitative research) with qualitative research methods and uses the approach of educational sociology. The subject of this research is the PAI Middle School teacher in Tempel sub-district and the object of this study is the social role of the PAI teacher in the community. To obtain data, data collection techniques are used through observation, interviews, and documentation. Data analysis method with inductive method. The results of this study stated that: 1) The reasons that encouraged PAI SMP teachers in Tempel sub-district to play a role in the community were internal encouragement (the ability to carry out roles and calls as a form of implication from the PAI teacher profession) and external encouragement (special views from the community , forms of accountability for their rights and obligations in social interactions and religious conditions of the community). 2) Forms of social roles are carried out in an inclusive, objective, non-discriminatory, adaptive and communicative manner which is manifested in the religious field (priests and preachers, preachers, mosque administrators, administrators of religious organizations) and non-religious (PKK administrators and RT heads) by playing a role in it as a guide and advisor, as a model and role model, as a innovator and as a motivator. 3) The social role played by PAI SMP teachers in Tempel sub-district gets different responses from the community. Positive response in the form of support, willingness to be involved, and desire to maintain the role of PAI teachers. Meanwhile, negative responses were shown by the community by not wanting to follow the ideas of PAI teachers because they were not in accordance with the culture of the community.